Monetary policy transmission: the case of Lithuania - Julius Stakenas; Rasa Stasiukynaite (Baltic Journal of Economics, 2017)
We study the effect of a (standard) monetary policy shock in the euro area on the Lithuanian economy. We employ a structural vector autoregressive model incorporating variables from both the euro area and Lithuania. The model exhibits a block exogenous structure to account for the fact that Lithuania is a small economy. In general, we find that a monetary policy shock in the euro area has a stronger effect on the Lithuanian than it does on the euro area economy, though the effects are not statistically significant, preventing firm conclusions. We further broaden our analysis employing a panel vector autoregression (PVAR) model for the three Baltic states. PVAR model results suggest a stronger impact of monetary policy than that estimated using the Lithuanian model and a quite considerable degree of variation over time in the strength of monetary policy transmission.
Keywords: E31; E52; C32; C33; 330; Monetary policy; euro area; SVAR; panel VAR